Response of Sugar Beet (Beta vulgaris L.) Growth, Yield and Yield Components to Compost and Phosphorus Fertilizers - A. Marajan Wael.; Eldin. M. Idris Baha; Haroun Mohamed Adam Abubaker (Journal of Agronomy Research, 2021)
Sugar beet is one of the sugar crops which widely grown in different regions of the world due to its advantages over Sugarcane. Several studies were conducted in Sudan to assess its adaptation and economic value. However, the aim of this experiment was to study the effect of application of compost and different levels of phosphorus fertilizer and their combination on Sugar beet (Beta vulgaris) growth attributes, yield and yield components. The study was conducted during the winter season 2018 –2019 at the farm of the College of Agriculture, University of Bahri, Alkadaro-Khartoum State, Sudan. The experiment was arranged in Randomized Complete Block Design (RCBD) with three replications and six treatments, namely the Compost (5t./ha.), Phosphorous (P2O5) (88kg./ha.), P2O5 (176 kg./ha.), Compost (5t./ha.)+P2O5 (88kg./ha.), Compost (5t./ha.)+ P2O5 (176Kg./ha.) and the Control (C) respectively. All cultural practices were carried out timely according to the recommendations of the Agricultural Research Centre in Sudan. Then the data pertaining the following agronomic traits were recorded, the leaf number; leaf dry weight (g), leaf area index (LAI) (cm), root diameter (RD) (cm) and root fresh weight (RFW) (g). The results of statistical analysis revealed the application of compost in combination with phosphorus displayed significant increase at 5% level for the leaf number (22.75), leaf area index (5.23), leaf dry weight(36.78), root diameter(69.67) and root fresh weight (422.68), followed by the application of compost alone compared to the control and other treatments. The study concludes that the combination of compost and mineral fertilizer (P2O5) proved to increase all Sugar beet growth and yield parameters.
Keywords: Agronomic traits